G46(P) Progression of neurophysiological changes in a child with subacute sclerosing panencephalitis. (25th October 2020) - Lazenbury, A; Bhangu, N; Illingworth, M; Allen, D; Singh, J
Abstract : Subacute sclerosing panencephalitis (SSPE) is classically associated with characteristic electroencephalogram (EEG) features of periodic and stereotyped high voltage discharges. We present the electroclinical evolution in a case of SSPE in whom the typical changes were not initially evident. The patient is a fully immunized seven-year old boy with a six-month history of increasingly frequent atonic drops with behavioural change and cognitive decline. His initial EEG showed continuous high amplitude 1–2 Hz sharp and slow wave activity, which were frontally dominant with little change on midazolam infusion. Eight days later, the EEG had a diffusely slow background with anterior sharp waves in a periodic/semi-periodic fashion, with complexes every 1–2 seconds. A rapid neurocognitive decline ensued, characterized by fluctuating consciousness, visual impairment, aphasia and the emergence of dystonia, rendering him non-ambulant within weeks of hospital admission. The EEG evolved with a diffusely slow background with no periodic sharp waves, except occasionally in the temporal regions. MRI brain showed asymmetrical T2-weighted signal change in sub-cortical and deep white matter. Serial imaging demonstrated increasing widespread signal abnormality. SSPE was confirmed by CSF measles PCR. His EEG at ten weeks after presentation progressed to typical periodic sharp and slow wave complexes, occurring every 6–7 seconds. The clinical course and EEG add weight to the growing body of evidence of SSPE occurring in a younger than expected cohort across the UK and Europe. SSPE is a neurodegenerative disorder where early illness is known to have a higher association with development of measles related sequelae. At a time when vaccination uptake is at an all time low, increased awareness of the burden of measles is crucial to facilitate improved health promotion and vaccination uptake worldwide. SSPE should be considered in any child presenting with regression and seizures even if the EEG and neuroimaging are not initially wholly supportive.